2016
DOI: 10.1159/000443437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intervention in Mast Cell Function Before Reperfusion on Renal Ischemia-Reperfusion Injury in Rats

Abstract: Background/Aims: Mast cells are sparsely distributed in the kidneys under normal conditions; however, the number of mast cells increases dramatically during renal ischemia/reperfusion injury (RI/RI). When mast cells are stimulated, numerous mediators are released, and under pathological conditions, they produce a wide range of biological effects. The aim of this study was to investigate the effect of intervention in mast cell function before reperfusion on RI/RI. Methods: Sprague-Dawley (SD) rats (n=50) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Of note in this context, Baba et al (55) recently showed in a rat model of chronic renal failure unchanged fibrosis progression after tranilast treatment, a potent MC stabilizer. Thus, our data strongly support that the degree of initial injury by MCs represents the major factor of pathologic development, calling for early MC-targeting therapeutic interventions as suggested recently (41).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Of note in this context, Baba et al (55) recently showed in a rat model of chronic renal failure unchanged fibrosis progression after tranilast treatment, a potent MC stabilizer. Thus, our data strongly support that the degree of initial injury by MCs represents the major factor of pathologic development, calling for early MC-targeting therapeutic interventions as suggested recently (41).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, recent data showed that treatment before reperfusion with cromolyn sodium or ketotifen, which are known MC stabilizers, markedly alleviated IRI-mediated kidney injury in rats, whereas exacerbated MC degranulation by compound 48/80 further aggravated kidney injury (41). Likewise, in another model of acute nephrotoxicity based on administration of the anticancer drug cisplatin, MCs were shown to significantly contribute to the initial renal injury by promoting neutrophil infiltration via the production of TNF (44).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TNF-α levels are associated with the development of nephropathy [13], with diverse actions potentially involved in the development of complications [14]. In type 2 diabetic patients, serum and urine TNF-α level increased significantly with the degree of albuminuria [15].…”
Section: Introductionmentioning
confidence: 99%
“…assessment of sOD activity and MDa level of renal tissues in DN Both SOD activity and MDA level were examined with the xanthine oxidase and thiobarbituric acid method. 25,26 SOD activity was measured after eight weeks ( Figure 10A). SOD activity in the DN group was less than in the sham group (P0.01; SOD activity: sham 76.32±2.39 U, DN group 31.25±1.45 U).…”
Section: Blood Glucose Levelsmentioning
confidence: 99%